Navigating Podcasts in the English Listening Classroom: A Library Research - Erniwati, Erniwati; Taqwim, Ahsani; Dewi, Anjar Kusuma; Arid, Muhammad (Lectura : Jurnal Pendidikan, 2025)
Podcasts, which consist of digital audio files, gains immense popularity as a technical resource for language acquisition, particularly among English language learners. The podcasts are attractive due to their flexibility, enabling learners to access language learning resources anytime and anywhere. This study was a-library research, comprising two categories of data. The primary data was sourced from a book entitled “Academic Podcasting and Mobile Assisted Language Learning" edited by Betty Rose Facer and Mohammed Abdoes, published in 2010. The secondary data were gathered from journal articles, seminar proceedings, and undergraduate’s thesis published from 2015 to 2023. The findings indicated that podcasts could serve as a valuable resource for boosting English language skills, especially listening skills. Whilst, factors affecting the effectiveness of using podcast in teaching listening skills were students’ motivation, accessibility to authentic materials, individual differences, teachers’ digital gap, and internet connectivity. Podcast provides some benefits when used in teaching listening skills. Podcasting utilizes authentic materials that can aid in the development of both receptive and productive language skills. It introduces the essence of language into the classroom, providing students with diverse forms of language input that can potentially improve their language proficiency. The podcast platform is user-friendly and easy to navigate. It encourages learners to take charge of their own learning, boosts their engagement and cognitive strategies, which in turn promote their ability to self-regulate during their studies, enhances critical thinking skills, offers extensive opportunities for collaborative and group learning, and increases their motivation to learn.